A study in preschool education in the Caribbean - Watson, Ena May (1981)
This investigation of different approaches to the provision of preschool services was stimulated by an increasingly strong concern in the Caribbean to create environments that foster the total development of young children in the region. The pilot survey of preschool settings was carried out in Jamaica where the range of service replicates those to be found in other parts of the region. The task of the investigation was to discover whether there are models of care which Caribbean countries, in developing their preschool services, can adapt to suit their individual circumstance. Critical questions posed by the data from the investigation and by discussions are: 1) How conducive are conditions in the various services to the creation of environments that are optimal for children's development? 2) How important are financial costs to the quality of the service provided? 3) What conclusions are to be reached from the investigation? and 4) What are the outstanding issues? A summary of the findings and conclusions reached are presented by way of responding to these questions
Keywords: Preschool centres